Case report: Successful use of mepolizumab for immune checkpoint inhibitors–induced hypereosinophilic syndrome in two patients with solid malignancies - Chiara Lazzari; Mona Rita Yacoub; Corrado Campochiaro; Alessandra Bulotta; Diego Palumbo; Francesca Rita Ogliari; Lorenzo Dagna; Silvia Marchesi; Maurilio Ponzoni; Maurilio Ponzoni; Vanesa Gregorc (Frontiers in Oncology, 2023)
Hypereosinophilic syndrome (HES) represents a group of blood disorders characterized by an absolute eosinophil count (AEC) > 1.5 × 103/μl in the peripheral blood, which eventually extravasate and cause organ damage. It can be primary or secondary to infections or tumors. The infiltration of eosinophils in tissue and organs is associated with different disorders and, in some cases, with life-threatening manifestations. Albeit the pathogenesis of HES in patients with solid tumo\rs is not yet clarified; recently, HES has also been described as an immune-related adverse event in patients with solid tumors receiving immune checkpoint inhibitors. Treatment of HES is still debated, especially in patients with concomitant solid tumors, and different drugs including imatinib, hydroxyurea, interferon-ɑ, glucocorticoids, and the monoclonal antibody targeting circulating IL-5 mepolizumab have been proposed according to the underlying cause and the severity of HES. Herein, we describe, for the first time, the successful use of mepolizumab for the treatment of immune checkpoint–induced HES in two patients with metastatic solid tumor.